Implementation of Environmental Parameter Control System in Green House to Increase Vegetable Production - Amelia, Afritha; Sundawa, Bakti Viyata; Roslina; Rahman, Rahimah Abdul (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The use of green houses in plant cultivation is one way to approach optimal conditions for plant growth. Green houses are generally useful for protecting plants from extreme air temperatures. This requires further study of the smart features that will be built to support the concept of greenhouse agriculture. The development of automation technology is expected to help the monitoring system of parameters that affect the production of vegetable crops such as air temperature, and air humidity. These parameters will be monitored remotely using the Internet of Things (IoT) method. Based on the measurement results from the location at POLMED campus. For Medan Selayang the maximum temperature is 26.4oC and humidity is 68.8%. For the location in Medan Johor the maximum temperature is 25.4oC and humidity is 68.1%. For Medan Baru location, the maximum temperature is 25.1oC and humidity is 68.3%. For Medan Helvetia location, the maximum temperature was 24.7oC and humidity was 69%. Based on the test results, the temperature and humidity parameters can be monitored remotely by 106.4 km via the internet.